Leadership In Developing A Culture Of Quality (Case Study In Madrasah Aliyah Negeri Lamongan) - Wahananto, Juri; Noviyanti, Shobihatul Fitroh; Nasyiri, Ahmad Nabil (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Quality human resources are becoming crucial in an era of globalization. Quality human resources are produced by quality educational institutions and led by the head of the madrasah, which consistently improves the quality of madrasas. Therefore, to improve the quality of the madrasah, it is necessary to build a culture of quality. Leadership plays an important role in shaping a solid madrasa culture of quality. Based on the above considerations, the study aims to (1) describe the leadership style of the Madrasa in developing a quality madrasa culture, (2) describe the leadership steps of the head of the madrasas in the development of a quality madrasah culture, (3) describe a cultural reality of the quality of Madrasa, (4) explain the efforts of the leader of the Madrasa in removing resistance to the quality culture development. This type of research is field research with a qualitative approach using case studies and data collection techniques through in-depth interviews, observations of participants, and documentation. Analysis of research results shows that (1) the main madrasa style in developing a quality culture has five leadership styles: charismatic, democratic, participatory, deliberative, and aggressive. It's adapted to the situation and conditions. (2) Leadership steps in developing a culture of quality madrasa: (a) the head of the Madrasa articulates the vision and mission of impact on improving the quality culture of Madrasa. (b) The head of the Madrasa has the values of leadership that are believed to be translated into the life of the organization of the madrasas. (c) the symbol is a description of the organizational values that rained and preserved and reflect the uniqueness of the Madrasas; (d) the process of development of a quality culture passes through four stages, namely the preparation phase, the acceptance phases, the implementation phases and the commitment phases. (3) The cultural reality of the quality of MAN Lamongan is related to the values of the institution and the leadership of the head of the Madrasa in promoting relations with the staff. (4) The individual teacher's resistance exists in developing a culture of madrasa-quality. The head of the Madrasa's efforts in dealing with the resistance of the people of Madrasa used a preventive and healing approach.